Social Representations and the AIDS Field - Joffe, Helene (PINS-Psychology in Society, 2026)
Social representations theory is evaluated with a view to ascertaining the contribution it makes to the AIDS field. Utilising a primarily European body of research, the various processes involved in social representation formation, and the functions served by social representations, are explicated. Social representations theory's fundamental contribution to the AIDS field is to enhance understanding of how lay people make meaning of the epidemic. Rather than focusing on how individuals process information about risks, the concern is with group-based understandings of health issues. The impetus towards identity protection motivates, and informs the shape of, the social representations of AIDS which emerge in a particular group.